Molecular cloning of mRNA sequences encoding rat lens crystallins. - Dodemont, H J (1981)
To provide access to crystallin-specific DNA sequences, we have constructed plasmid clones bearing duplex DNA sequences complementary to crystallin mRNAs isolated from rat lens. Optimization of the cDNA reaction conditions enabled us to fractionate three double-stranded (ds) cDNA groups. Molecular cloning of dC-tailed ds cDNAs into the Pst I site of dG-tailed pBR322 yielded crystallin-specific clones of each group. By means of positive hybridization selection and translation, recombinant plasmids containing cDNA sequences coding for rat lens polypeptides from alpha-, beta-, and gamma-crystallins could be identified. The established cDNA clones have been used for a blot-hybridization analysis to map the crystallin mRNAs from which they originated. Both procedures revealed a high degree of homology between the gamma-crystallin sequences. From the beta-crystallin class, the beta H-specific cDNA coding for the beta B1a polypeptide was obtained. The alpha A-chain clone did not show any cross-hybridization to the alpha B-chain mRNA despite the existence of 60% homology between the corresponding gene products. As this clone hybridized to both alpha A2 and alpha AIns mRNAs, sequence analysis was applied for further characterization. The results showed that the cloned cDNA corresponds to the alpha A2 sequence exclusively.